2012
DOI: 10.5511/plantbiotechnology.12.0418a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the casbene synthase homolog from Jatropha (<i>Jatropha curcas</i> L.)

Abstract: Abstracte high oil content of Jatropha (Jatropha curcas L.) seeds makes Jatropha an attractive resource for the production of sustainable bioenergy. However, the Jatropha seed kernels also contain antinutrients and various toxins that persist in the oil and seed cakes and pose a safety risk. Since phorbol esters (PEs) are the major contributor to toxicity, a better understanding of PE biosynthesis is expected to elucidate an e ective strategy for the utilization of Jatropha plants. In this study, a Jatropha cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…diterpene synthases demonstrated a common H-bond network (SI Appendix, Fig. S1 D and E) (27,29,(33)(34)(35)(36)(37)(38)(39)(40)(41). This suggests that a conserved basic amino acid-rich triad sets and holds PP i in place during the complete catalytic cascade.…”
Section: Txs•ggpp Complex: Evolutionarily Conserved Motifs Initiate Thementioning
confidence: 94%
“…diterpene synthases demonstrated a common H-bond network (SI Appendix, Fig. S1 D and E) (27,29,(33)(34)(35)(36)(37)(38)(39)(40)(41). This suggests that a conserved basic amino acid-rich triad sets and holds PP i in place during the complete catalytic cascade.…”
Section: Txs•ggpp Complex: Evolutionarily Conserved Motifs Initiate Thementioning
confidence: 94%
“…The reaction cascade is either initiated by a metal iondependent ionization of the diphosphate moiety or a protonation of the substrate, and can be terminated by proton abstraction or water addition (11,13,15). Because the reaction cascade may be branched and termination may occur at multiple levels, many TPSs are multiproduct enzymes forming complex mixtures of compounds (16)(17)(18)(19). Moreover, some TPSs also accept multiple substrates to produce monoterpenes, sesquiterpenes, and diterpenes (11).…”
mentioning
confidence: 99%
“…Little information about the biosynthetic pathway of phorbol ester has been elucidated. However, a recent study reported that Casbene Synthase (CS) might be involved in the first step of tiglian cyclization [15]. This report suggests that CS might be an essential enzyme, which regulates the biosynthetic of phorbol esters.…”
Section: In Silico Analysis Of Casbene Synthase Among Euphorbiaceae Pmentioning
confidence: 94%
“…J. curcas Casbene Synthase (JcCS) has been identified and reported that JcCS is expressed in seedlings, mature leaves and in the mesocarp of developing fruits. Nevertheless, it is not expressed in developing seeds [15]. For a better understanding of the CS of several Euphorbiaceae, we analyzed the sequence of CS of six Euphorbiaceae plants, including J. curcas (XP_012066843), Ricinus communis (XP_002513340), Triadica sebifera (ADB90272), Euphorbia fischeriana (AFQ98015), Euphorbia esula (ADB90273) and Euphorbia peplus (AGN70884).…”
Section: In Silico Analysis Of Casbene Synthase Among Euphorbiaceae Pmentioning
confidence: 99%
See 1 more Smart Citation